Video Blog (Vlog): Media Innovation in Mathematics Learning explores creative mathematics learning - Zahroh, Umy; Ariansyah, Fitroh; Farooq, Syed Muhammad Yousaf (Journal of Teaching and Learning Mathematics, 2024)
Students often need help acquiring information about mathematics delivered in class within a limited timeframe, without the opportunity for repeated discussions or comprehensive review. Additionally, retaining previously taught material might be challenging. Hence, educators must establish efficacious instruction that stems from pioneering pedagogy. One of the advancements is the utilization of educational media. This study examines the existing literature about using video blogs (vlogs) as a medium for educational purposes. This study employs the Systematic Literature Review (SLR) methodology. Data was gathered by systematically collecting and scrutinizing articles about vlogs as an educational medium published between 2013 and 2023. This research utilized eight papers, theses, and dissertations from reputable national journals or conferences. The materials were collected through the Publish or Perish tool. The research findings indicate that including vlog media in the learning process can enhance the efficacy of instruction and positively impact students' learning outcomes. Thus, vlogs can be utilized as an educational tool for mathematics instruction. The essay provides a comprehensive analysis of the practicality of this innovation in enhancing mathematics education.